Pengaruh Literasi Digital, Pelatihan Online, dan Kepuasan Kerja terhadap Produktivitas Karyawan di Startup Digital - Diana Nopiar Fitriani; Diana Putri; Intan Kharisma Dewi; Eteh Resa Asyifa (Journal of Innovative and Creativity, 2026)
The increasingly rapid development of technology has had a significant impact on work systems and patterns, especially in digital startup-based companies. Employees in digital startup companies are required to have adequate digital skills to be able to adapt to internetbased technology, virtual work systems, and various digital platforms used as productivity tools. This study aims to determine the effect of digital literacy, online training, and job satisfaction on employee productivity in digital startups. The research method used is a quantitative method with an associative approach. The sample size in this study was 30 respondents who were digital startup employees. Data collection was carried out using a questionnaire based on the indicators of each research variable. The research instrument was first tested through validity and reliability tests before being distributed to all respondents. Data analysis used the classical assumption test, multiple regression test, determination coefficient test, F test (ANOVA), and t test (coefficient). The results of the study indicate that digital literacy, online training, and job satisfaction have a positive and significant effect on employee productivity. This means that the higher the digital literacy, the more effective the online training received, and the better the level of employee job satisfaction, the higher the employee productivity in digital startup companies. This research is expected to serve as a reference for companies in improving digital competence and work well-being to support employee productivity.